MODEL KEMITRAAN DALAM POLA PEMBIAYAAN PERKEBUNAN SAWIT - Zamzami, Zamzami (Jurnal Paradigma Ekonomika, 2011)
Palm plantations is one of the relatively advanced plantations in Indonesia. One of the most developed model of partnership is the PIR-Bun. Where large companies as a nucleus and Farmers as plasma. With the relative number of the application of the PIR-Bun, the more rapid development of oil palm plantations.